DEVELOPING SCREENCAST O MATIC AS MEDIA OF WRITING DESCRIPTIVE TEXT FOR GRADE EIGHTH STUDENTS IN JUNIOR HIGH SCHOOL - Sri Suci Batubara; Nora Ronita Dewi; Farida Hanim Saragih (Universitas Negeri Medan, 2018)
This study aims to design Screencast O Matic as media of writing descriptive text for grade eighth students in Junior High School. The research was conducted by Research and Development (R & D) design through six stages; gathering information and data, analyzing the data, designing new writing media, validating to experts, revising writing media, and final product. The subject of this research was grade eighth students at SMP Negeri 27 Medan. The instruments used for collecting the data were interview and questionnaire. The data were gathered by administering interview to the English teacher and distributing questionnaire to 30 respondents to get the students’ needs in learning descriptive text. The writing media have been validated by two experts, English teacher and English lecturer. The average score from English teacher and English lecturer was 90,4% so it was categorized as Very Good. It means the developing Screencast O Matic as media of writing descriptive text is appropriate for grade eighth students in Junior High School. Keywords: Research and Development (R&D), Writing media, Descriptive text, Screencast O Matic